Characterization of Collagen Binding Activity of Clostridium perfringens Strains Isolated from Broiler Chickens - Zhifeng Sun; Mingmin Lu; Hyun Lillehoj; Youngsub Lee; Doyun Goo; Baohong Yuan; Xianghe Yan; Charles Li (Pathogens, 2023)
Clostridium perfringens is the etiological agent for necrotic enteritis (NE) in broiler chickens, which causes a substantial economic loss of an estimated USD 6 billion annually in the global poultry industry. Collagen adhesion is involved in the NE pathogenesis in poultry. In this study, the binding capabilities of chicken C. perfringens isolates of various genetic backgrounds (netB−tpeL−, netB+tpeL−, netB+tpeL+) to collagen types I–V and gelatin were examined, and the putative adhesin protein cnaA gene was investigated at the genomic level. In total, 28 C. perfringens strains from healthy and NE-inflicted sick chickens were examined. The results on collagen adhesin-encoding gene cnaA by the quantitative-PCR results indicated that netB−tpeL− isolates had much lower copies of the detectable cnaA gene than netB+ isolates (10 netB+tpeL− isolates, 5 netB+tpeL+ isolates). Most of the virulent C. perfringens isolates demonstrated collagen-binding abilities to types I–II and IV–V, while some strains showed weak or no binding to collagen type III and gelatin. However, the netB+tpeL+ isolates showed significantly higher binding capabilities to collagen III than netB−tpeL− and netB+tpeL− isolates. The data in this study suggest that the collagen-binding capability of clinical C. perfringens isolates correlates well with their NE pathogenicity levels, especially for C. perfringens isolates carrying genes encoding crucial virulence factors and virulence-associated factors such as netB, cnaA, and tpeL. These results indicate that the presence of the cnaA gene may be correlated with C. perfringens virulence (particularly for netB+ isolates).